Nanofibrous insulin/vildagliptin core-shell PLGA scaffold promotes diabetic wound healing - Lee, Chen-Hung; Chen, Dong-Yi; Hsieh, Ming-Jer; Hung, Kuo-Chun; Huang, Shu-Chun; Cho, Chia-Jung; Liu, Shih-Jung (Frontiers in Bioengineering and Biotechnology, 2023)
Slow wound repair in diabetes is a serious adverse event that often results in loss of a limb or disability. An advanced and encouraging vehicle is wanted to enhance clinically applicable diabetic wound care. Nanofibrous insulin/vildagliptin core-shell biodegradable poly (lactic-co-glycolic acid) (PLGA) scaffolds to prolong the effective drug delivery of vildagliptin and insulin for the repair of diabetic wounds were prepared. To fabricate core-shell nanofibrous membranes, vildagliptin mixture with PLGA, and insulin solution were pumped via separate pumps into two differently sized capillary tubes that were coaxially electrospun. Nanofibrous core-shell scaffolds slowly released effective vildagliptin and insulin over two weeks in vitro migration assay and in vivo wound-healing models. Water contact angle (68.3 ± 8.5o vs. 121.4 ± 2.0o, p = 0.006) and peaked water absorbent capacity (376 ± 9% vs. 283 ± 24%, p = 0.003) of the insulin/vildagliptin core-shell nanofibrous membranes remarkably exceeded those of a control group. The insulin/vildagliptin-loaded core-shell nanofibers improved endothelial progenitor cells migration in vitro (762 ± 77 cells/mm2 vs. 424.4 ± 23 cells/mm2, p < 0.001), reduced the α- smooth muscle actin content in vivo (0.72 ± 0.23 vs. 2.07 ± 0.37, p < 0.001), and increased diabetic would recovery (1.9 ± 0.3 mm2 vs. 8.0 ± 1.4 mm2, p = 0.002). Core-shell insulin/vildagliptin-loaded nanofibers extend the drug delivery of insulin and vildagliptin and accelerate the repair of wounds associated with diabetes.